Knowledge, Attitudes, and Practices of Saudi Citizens on COVID-19 Pandemic: A Multi-region Survey - Alreshidi, Maha Sanat; Alreshidi, Nojoud Abdullah Daaya; Felemban, Ebaa; Gonzales, Ferdinand (UI Scholars Hub, 2021)
Background: Although policies and guidelines may not always be optimal in all settings, a tailor-fitted guideline is appropriate. This study aims to determine the differences in the knowledge, attitudes, and practices (KAP) of Saudi citizens toward Coronavirus Disease 2019 (COVID-19). Methods: A quantitative-comparative-correlational approach was carried out from March 21 to May 22, 2020. Descriptive statistics, ANOVA, and t-test were used to determine the differences in knowledge and demographic characteristics. Linear regression was used to determine relationships among KAP. Results: The participants’ knowledge yielded 82.83%, positive attitudes (M = 2.10; SD = 1.15) and good practices (M = 2.10; SD = 1.15). Significant differences in knowledge were found for gender (t = −6.79; p < 0.001), marital status (F = 10.59; p < 0.001), education (F = 32.46; p < 0.001), occupation (F = 6.79; p < 0.001), and area of residence (F = 7.53; p <.001). Knowledge and practices showed a significant relationship (p < 0.001). Conclusions: Gender, marital status, education, occupation, and area of residence are all causal factors that differ regarding knowledge. Moreover, a significant relationship between knowledge and practice is established, which is necessary to improve. These study results can serve as a basis for creating effective health education programs toward COVID-19.